Theoretical analysis of a proposed InAs/InAsSb heterojunction photodetector for mid-infrared (MIR) applications - Lal R.K.; Jain M.; Gupta S.; Chakrabarti P. (My University, 2025)
The authors propose a single heterojunction InAs/InAsSb photovoltaic detector for application in the mid-infrared region at room temperature. A closed form physics-based analytical model of the device has been developed for characterisation of the device. Numerical computations have been carried out on the basis of the model for a P+-InAs/n0-InAs 0.88Sb0.12/n+-InAs0.88Sb 0.12 heterojunction photodetector to explore the potential of the device for possible non-telecommunication applications in the 2.5-4.5 μm wavelength region. The present model takes into account the effects of radiative recombination, Auger recombination, surface recombination and tunnelling at the hetero-interface on the detectivity of the device. The model enables the performance of the device to be optimised in terms of detectivity, responsivity and quantum efficiency. The model also provides useful design guidelines for fabrication of single heterojunction InAsSb photovoltaic detectors grown on InAs substrates. It has been observed that the doping concentration in the lightly doped active region, surface recombination and tunnelling at the hetero-interface strongly influence the performance of the InAs/InAs0.88Sb0.12 detectors.